Maternal vgll4a regulates zebrafish epiboly through Yap1 activity - Camacho-Macorra, Carlos; Tabanera, Noemí; Sánchez-Bustamante, Elena; Bovolenta, Paola; Cardozo, Marcos J. (Frontiers in Cell and Developmental Biology, 2024)
Gastrulation in zebrafish embryos commences with the morphogenetic rearrangement of blastodermal cells, which undergo a coordinated spreading from the animal pole to wrap around the egg at the vegetal pole. This rearrangement, known as epiboly, relies on the orchestrated activity of maternal transcripts present in the egg, compensating for the gradual activation of the zygotic genome. Epiboly involves the mechano-transducer activity of yap1 but what are the regulators of yap1 activity and whether these are maternally or zygotically derived remain elusive. Our study reveals the crucial role of maternal vgll4a, a proposed Yap1 competitor, during zebrafish epiboly. In embryos lacking maternal/zygotic vgll4a (MZvgll4a), the progression of epiboly and blastopore closure is delayed. This delay is associated with the ruffled appearance of the sliding epithelial cells, decreased expression of yap1-downstream targets and transient impairment of the actomyosin ring at the syncytial layer. Our study also shows that, rather than competing with yap1, vgll4a modulates the levels of the Ecadherin/β-catenin adhesion complex at the blastomeres' plasma membrane and hence their actin cortex distribution. Taking these results together, we propose that maternal vgll4a acts at epiboly initiation upstream of yap1 and the E-cadherin/β-catenin adhesion complex, contributing to a proper balance between tissue tension/cohesion and contractility, thereby promoting a timely epiboly progression.